Retention strength of cobalt-chromium vs nickel-chromium titanium vs Cp titanium in a cast framework association of removable partial overdenture - Souza, José Everaldo de Aquino; da Silva, Nelson Renato França Alves; Coelho, Paulo Guilherme; Zavanelli, Adriana Cristina [UNESP]; Ferracioli, Renata Cristina Silveira Rodrigues; Zavanelli, Ricardo Alexandre (Jaypee Brothers Medical Publishing, 2011)
Aim: There is little information considering the framework association between cast clasps and attachments. The aim of this study was to evaluate the retention strength of frameworks match circumferential clasps and extra resilient attachment cast in three different alloys (cobalt-chromium, nickel-chromium titanium and commercially pure titanium), using two undercut (0.25 and 0.75 mm) and considering different period of time (0, 1/2, 1, 2, 3, 4 and 5 years). Methods: Using two metallic matrices, representing a partially edentulous mandibular right hemiarch with the first molar crown, canine root and without premolars, 60 frameworks were fabricated. Three groups (n = 20) of each metal were cast and each group was divided into two subgroups (n = 10), corresponding the molar undercut of 0.25 mm and 0.75 mm. The nylon male was positioned at the matrix and attached to the acrylic resin of the prosthetic base. The samples were subjected to an insertion and removal test under artificial saliva environment. Results: The data were analyzed and compared with ANOVAs and Tukey's test at 95% of probability. The groups cast in cobaltchromium and nickel-chromium-titanium had the highest mean retention strength (5.58 N and 6.36 N respectively) without significant difference between them, but statistically different from the group cast in commercially pure titanium, which had the lowest mean retention strength in all the periods (3.46 N). The association frameworks using nickel-chromium-titanium and cobalt-chromium could be used with 0.25 mm and 0.75 mm of undercut, but the titanium samples seems to decrease the retention strength, mainly in the 0.75 mm undercut. The circumferential clasps cast in commercially pure titanium used in 0.75 mm undercuts have a potential risk of fractures, especially after the 2nd year of use. Conclusion: This in vitro study showed that the framework association between cast clasp and an extra resilient attachment are suitable to the three metals evaluated, but strongly suggest extra care with commercially pure titanium in undercut of 0.75 mm. Clinical significance: Frameworks fabricated in Cp Ti tend to decrease in retentive strength over time and have a potential risk of fracture in less than 0.75 mm of undercut.
Keywords: Dental clasps; Denture precision attachment; Removable partial denture; chromium derivative; cobalt; dental alloy; titanium; analysis of variance; comparative study; dental procedure; dental surgery; denture; instrumentation; materials testing; nonparametric test; Young modulus; Analysis of Variance; Chromium Alloys; Cobalt; Dental Alloys; Dental Casting Technique; Dental Clasps; Dental Stress Analysis; Denture Design; Denture Precision Attachment; Denture Retention; Denture, Overlay; Denture, Partial, Removable; Elastic Modulus; Materials Testing; Statistics, Nonparametric; Titanium; Tooth Preparation, Prosthodontic